Regional Autonomy and Local Democracy: Independent Candidates Cases - Suryanto, Suryanto; Hidayat, Tony Murdianto (Jurnal Bina Praja, 2016)
One of the efforts to achieve local democracy is through the participation of independent candidates in the Direct General Election in the region. The presence of independent candidates in the Direct General Election gives a great hope to change the political structure of the shackles of the old forces. This paper aims to discuss the implication of regional heads coming from independent candidates on the effectiveness of local governance and the implementation of substantive democracy in the region. The method used is a qualitative approach using descriptive research method. The data collection is done through literature approach. Processing data uses Milles and Huberman interactive models, which includes data reduction, data presentation, and conclusion. The study concluded three things: First, the presence of independent candidates in the Direct General Election gives the opportunities to achieve local democracy that is getting bigger, Second, Regional Heads elected from independent candidates face the challenges of the ineffectiveness of regional government, and Third, within certain limits, the power of elected regional heads from independent lane leads to the realization of democracy that is not substantial.